Preconditioning with selective autoretroperfusion: In vivo and in silico evidence of washout hypothesis - Choy, Jenny S.; Hubbard, Terry; Wang, Haifeng; Awakeem, Yousif; Khosravi, Pouya; Khadivi, Bahram; Navia, Jose A.; Stone, Gregg W.; Lee, Lik Chuan; Kassab, Ghassan S. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction. Prompt reperfusion of coronary artery after acute myocardial infarction (AMI) is crucial for minimizing heart injury. The myocardium, however, may experience additional injury due to the flow restoration itself (reperfusion injury, RI). The purpose of this study was to demonstrate that short preconditioning (10 minutes) with selective autoretroperfusion (SARP) ameliorates RI, based on a washout hypothesis. Methods. AMI was induced in 23 pigs (3 groups) by occluding the left anterior descending (LAD) artery. In SARP-b (SARP balloon inflated) and SARP-nb (SARP balloon deflated) groups, arterial blood was retroperfused for 10 minutes via the great cardiac vein before releasing the arterial occlusion. A mathematical model of coronary circulation was used to simulate the SARP process and evaluate the potential washout effect. Results. SARP restored left ventricular function during LAD occlusion. Ejection fraction in the SARP-b group returned to baseline levels, compared to SARP nb and control groups. Infarct area was significantly larger in the control group than in the SARP-b and SARP-nb groups. End-systolic wall thickness was preserved in the SARP-b compared to the SARP-nb and control groups. Analyte values (pH, lactate, glucose, and others), measured every 2 minutes during retroperfusion, suggest a “washout” effect as one important mechanism of action of SARP in reducing infarct size. With SARP, the values progressively approached baseline levels. The mathematical model also confirmed a possible washout effect of tracers. Discussion. RI can be ameliorated by delaying restoration of arterial flow for a brief period of time while pretreating the infarction with SARP to restore homeostasis via a washout mechanism.